Differences Between Soy Milk and Papaya Leaf Juice in Overcoming Low Milk Production in Breastfeeding Mothers at Cikeusal Health Center - Udur Diana Tumanggor; Dian Wahyu Ratri; Dita Listianinghias; Elin Erlina; Rohimah; Wiwin Pitriani (Jurnal Penelitian Pendidikan IPA, 2025)
Adequate breast milk production is essential for infant growth and development. However, many breastfeeding mothers experience insufficient milk supply. Natural interventions such as consuming soy milk and papaya leaf juice are believed to help increase breast milk production. Soy milk contains isoflavones that mimic estrogen and stimulate lactation, while papaya leaf juice contains saponins, alkaloids, and polyphenols that can enhance prolactin secretion and facilitate milk flow. This study aimed to determine the difference between the effects of soy milk and papaya leaf juice in overcoming low breast milk production among breastfeeding mothers at the Cikeusal Health Center in 2025. This quasi-experimental study involved 100 breastfeeding mothers with low milk production, divided into two groups using purposive sampling: 50 respondents received soy milk and 50 received papaya leaf juice. Each group was evaluated for changes in breast milk volume before and after the intervention. Data were analyzed using an independent sample t-test. The findings showed no significant difference between the two interventions (t = -0.639, p = 0.527). The mean increase in milk production after soy milk consumption was 27.10 ml, while papaya leaf juice increased milk production by 28.20 ml, with a difference of 1.1 ml. These results indicate that both soy milk and papaya leaf juice are effective in improving breast milk production, although their effects are statistically comparable. Both soy milk and papaya leaf juice can serve as alternative natural interventions to increase breast milk production in breastfeeding mothers. Health workers are encouraged to promote these natural options as supportive measures for mothers with low milk supply.